2021
DOI: 10.1007/s10669-021-09821-3
|View full text |Cite
|
Sign up to set email alerts
|

What are the drivers and barriers for green business practice adoption for SMEs?

Abstract: The depletion of natural resources as a byproduct of widespread, global economic growth has urged entrepreneurs to think about the environment when starting or conducting business. However, several of these smaller-sized firms struggle with implementing environmentally conscious business practices, especially Small and Medium Enterprises (SMEs), which represent more than 95% of all private sector firms. This study uses a survey method to assess and better comprehend the key drivers and barriers of green busine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
58
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(90 citation statements)
references
References 73 publications
(105 reference statements)
3
58
0
Order By: Relevance
“…, 2016; Yacob et al. , 2019) and it was found that most global pollution (up to 60–70%) is due to the SMEs' environmental impact (IFAC, 2019; Purwandani and Michaud, 2021). Hence, scholars emphasised that the role of SMEs is highly significant in achieving the environmental sustainability agenda in the economy.…”
Section: Review Of Literaturementioning
confidence: 99%
See 3 more Smart Citations
“…, 2016; Yacob et al. , 2019) and it was found that most global pollution (up to 60–70%) is due to the SMEs' environmental impact (IFAC, 2019; Purwandani and Michaud, 2021). Hence, scholars emphasised that the role of SMEs is highly significant in achieving the environmental sustainability agenda in the economy.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Hence, scholars emphasised that the role of SMEs is highly significant in achieving the environmental sustainability agenda in the economy. GR of the SME sector is predominantly focussed on mere conformity, mainly due to their resource poverty (Purwandani and Michaud, 2021; Salim et al. , 2018; Yacob et al.…”
Section: Review Of Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, there are conflicting interests between economic development versus biodiversity conservation in East Kalimantan, prompting dilemmas in policies and decision making. The development of the cement industry will likely impact the biodiversity in East Kalimantan altogether with habitat destruction, the rarity of biodiversity and overexploitation (Harrison et al 2020 ) Currently, the depletion of natural resources as a negative impact of global economic growth has raised the awareness among the business people to pay more attention to the environment and push them to implement more environmentally friendly practices, although there is still room for improvement to create the best practices for the environment (Purwandani and Michaud 2021). In the context cement industry in East Kalimantan, scientific studies are needed to bridge the gap between the development of the cement industry (along with the mining of limestone quarry) and biodiversity conservation.…”
Section: Introductionmentioning
confidence: 99%